Medicines transparency at the European Medicines Agency (EMA) in the new information age: the perspectives of patients. Issue 9 (20th October 2016) - Way, Dominic; Bouder, Frederic; Löfstedt, Ragnar; Evensen, Darrick
Abstract : The concept of transparency has gained widespread appeal in the European pharmaceutical domain, not least at the European Medicines Agency (EMA). Agency policies have two main objectives: (1) to enable the reuse of data (e.g. clinical study reports) and (2) to empower patients to directly and indirectly make more informed decisions on medicines. Past research has almost exclusively focused on the perspectives of external researchers intending to reanalyse data made publically available. Few studies, however, have explored what can be learnt from the perspectives of other actors (e.g. health care professionals, patients, the regulators themselves, industry and others). This empirical study explores the EMA's transparency policies from the perspectives of patients. After presenting the results of a survey ( N  = 1010) with a sample of individuals diagnosed with five specific medical conditions (HIV/AIDS, multiple sclerosis, rheumatoid arthritis, osteoporosis and idiopathic pulmonary fibrosis) from four EU countries (Germany, Spain, France and the UK), the authors argue that EMA's transparency policies do not adequately address the real-world complexities of communicating with patients. In turn, the paper concludes that the perspective of patients provides an essential contribution to understanding the full net effects (positive, negative and/or limited) of EMA's transparency policies.